2018
DOI: 10.1002/acm2.12249
|View full text |Cite
|
Sign up to set email alerts
|

Variations in dosimetric distribution and plan complexity with collimator angles in hypofractionated volumetric arc radiotherapy for treating prostate cancer

Abstract: PurposeHypofractionated radiotherapy can reduce treatment durations and produce effects identical to those of conventionally fractionated radiotherapy for treating prostate cancer. Volumetric arc radiotherapy (VMAT) can decrease the treatment machine monitor units (MUs). Previous studies have shown that VMAT with multileaf collimator (MLC) rotation exhibits better target dose distribution. Thus, VMAT with MLC rotation warrants further investigation.Methods and materialsTen patients with prostate cancer were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Our suggested method allows either an optimal static angle or a dynamic angle trajectory to be identified. The optimal static angle can be expected to provide a reduced delivery time compared to an ill‐suited angle for any tumor type that has a nonsymmetric shape in the beam’s‐eye‐view (BEV) . The use of a dynamic angle trajectory may provide additional time savings compared to the optimal static angle if the BEV projection of the target changes as a function of the gantry angle.…”
Section: Discussionmentioning
confidence: 99%
“…Our suggested method allows either an optimal static angle or a dynamic angle trajectory to be identified. The optimal static angle can be expected to provide a reduced delivery time compared to an ill‐suited angle for any tumor type that has a nonsymmetric shape in the beam’s‐eye‐view (BEV) . The use of a dynamic angle trajectory may provide additional time savings compared to the optimal static angle if the BEV projection of the target changes as a function of the gantry angle.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified the optimum collimator angles for optimizing dosimetric distribution for planning target volume (PTV), sparing of organs at risk (OARs), and plan complexity. The findings of this study could help planners to select appropriate collimator angles to obtain optimum results [8,9].…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies on the effect of collimator angle on VMAT plan quality proposed various optimal settings depending on the tumor site and shape 12 , 17 , 41 . For vertebrae metastases, Mancosu et al suggested a collimator angle of around 90° to align the MLC leaf motion with the spinal cord 41 .…”
Section: Discussionmentioning
confidence: 99%
“…For vertebrae metastases, Mancosu et al suggested a collimator angle of around 90° to align the MLC leaf motion with the spinal cord 41 . For prostate cancer, Li et al suggested an angle of 45° for the optimal dose distribution plan complexity 17 . For nasopharynx cancer, Otto found that 45° was preferable in most cases 12 .…”
Section: Discussionmentioning
confidence: 99%